An under‐forecast snowstorm associated with a small but deep tropopause depression. (25th November 2019) - Smart, David; Browning, Keith
Abstract : Three‐dimensional view of snow streamers producing heavy snowfall over southern England obtained from a T + 6h mesoscale model forecast valid at 1200 utc, 1 February 2019, showing a sub‐set of the computational domain 4km high and approximately 240 × 240km as viewed from the west. The 3D isosurface depicts a model reflectivity of 23dBZ, corresponding to a moderate snowfall intensity and has been shaded according to vertical air velocity according to the colour scale. Note the cellular and sloping nature of the streamers within the snow bands and the strong positive vertical velocities consistent with the presence of shallow 'generating' cells of upright convection at their top.